Administration of Islamic Law and Human Rights: The Basis and Its Trajectory in Malaysia - Farid Sufian Shuaib (Al-Jami'ah: Journal of Islamic Studies, 2018)
This paper looks at the interplay between the administration of Islamic law in Malaysia in relation to Islamic family law and Islamic criminal law; and human rights. The paper examines the basis of the administration of Islam in Malaysia in relation to its history and post-independence mandate. It looks at the position of human rights under the Federal Constitution and the position of the administration of Islamic law under the constitutional framework. The research found that entrenching fundamental liberties through the supremacy clause resulted in the prevalence of human rights over freedom of religion. However, this is not consistently arrived at since the constitutional frameworks allows for plurality of laws and exclusion of personal law from the principle of equality.[artikel ini membahas kelindan antara administrasi hukum islam, hukum keluarga islam, hukum pidana islam, dan HAM di Malaysia. Artikel ini berbasis pada sejarah administrasi Islam di Malaysia sebelum dan sesudah kemerdekaan. Pembahsan lain artikel mengamati posisi HAM di bawah Undang Undang Federal Malaysia dan administrasi hukum Islam dalam kerangka konstitusional. Berdasarkan hasil riset menunjukkan dasar kebebasan pada supremasi klausul perundangan yang cenderung lebih utama HAM daripada kebebasan beragama. Meskipun demikian, hal ini tidak selalu konsisten ketika perspektif konstitusi mengikuti pluralitas hukum dan eksklusi hukum personal dari prinsip kesetaraan.]